Pengaruh Tipe Kepribadian, Kontrak Psikologis, Komitmen Organisasi, motivasi Dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB) Dan Kinerja Karyawan Di Rumah Sakit ParuKabupaten Jember - Noer Aisyah Barlian (STIE Mandala Jember, 2016)
The proof of a success hospital is the awards received. Jember Chest Hospital from 2010 to 2014 became the champion in various awards in the field of services and work culture. Surely Jember Chest Hosnpital has employees who perform well and have behavioral Organizational Citizenship Behavior (OCB).Subjects were nurses as many as 71 people. Explanatory research method is used. Retrieving data using questionnaires. Data was analized using SEM (Structural Equestion Model). The result of research that variable personality type and organizational commitment and significant positive effect on Organizational Citizenship Behavior (OCB). Psychological contract variables, motivation and job satisfaction positive and significant impact on Organizational Citizenship Behavior (OCB). Variable type of personality and psychological contracts and no significant positive effect on employee performance. and variable organizational commitment, motivation, job satisfaction and Organizational Citizenship Behavior (OCB) positive and significant impact on employee performance.